Third solitudes : tradition and discontinuity in Jewish-Canadian literature - Greenstein, Michael (McGill-Queen's University Press, 1989)
Canadian-Jewish literature, Greenstein argues, is characterized by the sense of homelessness and exile which dominated the writings of the father of Jewish-Canadian literature, A.M. Klein. Greenstein finds the paradigm for this sense of loss in Henry Kreisel's short story, "The Almost Meeting." Using the theme of this story as a base, Greenstein describes how the Jewish-Canadian writer is divided between life in Canada and a rich European past - between life in the New World and the strong traditions of the Old. The Jewish-Canadian writer may look for a home in both these places, but neither is fulfilling as both are necessary parts of the individual. The writer thus straddles two incompatible worlds and must expect the loss of one or the other. In the struggle to overcome these difficulties and maintain a true dialogue with others and themselves, such writers experience missed or "almost meetings" as they cope with the homelessness that characterizes diaspora and Canada's "third solitude."